2020
DOI: 10.3390/w12061788
|View full text |Cite
|
Sign up to set email alerts
|

Experimental and Numerical Investigations of Hydraulics in Water Intake with Stop-Log Gate

Abstract: A stop-log gate, installed in water intake of hydropower project, has become an effective facility in achieving selective withdrawal and temperature control for the sake of benefiting downstream ecosystems. Hence, it is of great importance to comprehensively explore the water intake hydraulics with the gate, not limited to some specific case studies. This study deals, through laboratory experiments and numerical simulations, with flow features of such a gate-functioned intake. The physical model test is used t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 24 publications
0
7
0
Order By: Relevance
“…Selective water withdrawal is widely used in stratified reservoirs worldwide [12] for optimizing variables that collectively influence water quality (e.g., water temperature, dissolved oxygen concentration, turbidity) within the reservoir or for implementing natural downstream temperature regimes as a component of environmental flows [44]. Various types of infrastructure are adapted to achieve selective withdrawal, such as multi-level offtake towers, temperature-controlled curtains, floating outlets, pivoted pipes or stop-lot gates [52] and each infrastructure component has specific options and restrictions that influence its application. Outlet towers, for example, can only be used to withdraw water at specific depths, while pivoted pipes can be freely moved in the vertical direction to take out water over a continuous depth range.…”
Section: Selective Water Withdrawal and Its Influence On Growth Of P ...mentioning
confidence: 99%
“…Selective water withdrawal is widely used in stratified reservoirs worldwide [12] for optimizing variables that collectively influence water quality (e.g., water temperature, dissolved oxygen concentration, turbidity) within the reservoir or for implementing natural downstream temperature regimes as a component of environmental flows [44]. Various types of infrastructure are adapted to achieve selective withdrawal, such as multi-level offtake towers, temperature-controlled curtains, floating outlets, pivoted pipes or stop-lot gates [52] and each infrastructure component has specific options and restrictions that influence its application. Outlet towers, for example, can only be used to withdraw water at specific depths, while pivoted pipes can be freely moved in the vertical direction to take out water over a continuous depth range.…”
Section: Selective Water Withdrawal and Its Influence On Growth Of P ...mentioning
confidence: 99%
“…Studies have shown that deeper withdrawal could facilitate heat transfer in the water column, increase the thickness of the metalimnion and weaken strati cation stability (Casamitjana et al, 2003;Ma et al, 2008). When the intake moves upward, the thermocline deepens, the withdrawal height controls the thermocline depth in summer, and the in ow depth and hydrodynamics are affected simultaneously (Mauric et al, 2021;Ren et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Reservoirs with a single outlet might release water that is too warm or too cold for downstream ecosystems, depending on reservoir temperature at the intake [ 3 ]. Currently, considering the severe effect of bottom-intake for withdrawal on ecology [ 12 , 13 ], which was commonly employed in some north temperate countries in the 1960s, selective withdrawal systems have been widely used to meet downstream temperature and other water quality objectives [ 14 , 15 ], such as stoplog gates [ 16 ] and temperature-control curtains (TCCs) [ 17 ]. With the objective of water quality changing, applying a selective withdrawal facility to a certain reservoir involves many factors such as the improvement effect of outflow temperature, reservoir operation and management mode, economic investment, safety performance and so on [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…Stop-log gates can mitigate the cold temperature effect in spring and summer [ 27 ]. Moreover, stoplog gates can influence the flow patterns including the flow regime and velocity distribution at the intake and the flow velocity at the trash rack section varies vertically in a great manner [ 16 ]. Thus, for distinct water management requirements, both relevant selective withdrawal systems and corresponding thermal properties may have a certain gap.…”
Section: Introductionmentioning
confidence: 99%